FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA DEPRESI PADA LANSIA DI WILAYAH KERJA PUSKESMAS MALA-MALA KABUPATEN KOLAKA UTARA - Andi Maryam; Andi Elis, Kasmawati (CV. ADIBA AISHA AMIRA, 2022)
The elderly are the group most prone to depression. Basically, elderly people will lose their zest for life, especially if they have thought about various desires that have not been fulfilled so far, feelings of guilt towards their family or partner will further encourage depression to become more severe. The purpose of this study was to determine the factors that influence the occurrence of depression in the elderly in the working area of the Mala- Mala Public Health Center, North Kolaka Regency. The type of research used is a Cross Sectional study. The sample in this study is part of the elderly population in the working area of the Mala-Mala Health Center Kab. North Kolaka as many as 44 people with a sampling technique that is purposive sampling. The results of the study obtained that the value of the lonely factor obtained a value of 0.044 < a = 0.05, the family support factor obtained a value of 0.042 < a = 0.05, the education factor obtained a value of 0.006 < a = 0.05 and the marital status factor obtained value of 0.044 < a= 0.05. The conclusion in this study are the factors that influence the occurrence of depression in the elderly in the working area of the Mala- Mala Health Center Kab. North Kolaka is a factor of loneliness, family support, education and marital status. Suggestions are expected to the government and related health agencies so that they can intensify programs that focus on preventing and overcoming depression in the elderly, and are expected to provide counseling, guidance, and direction to the elderly on the incidence of depression that can be experienced by the elderly and can improve their health status